2023
DOI: 10.1038/s41598-023-28767-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining mediators of associations of food insecurity and being bullied with suicide among in-school adolescents in Eswatini: a cross-sectional study

Abstract: We examined the potential mediating roles of anxiety and loneliness on the association of concurrent food insecurity (FI) and being bullied (BB) with suicidal behavior (SB) in Eswatini, a lower-middle-income country. We used data from the Global School-based Student Health Survey (GSHS; N = 3264), which employed a two-stage cluster sampling: first, 25 schools were selected based on the proportionate probability of enrollment; second, classes were randomly selected. A self-reported 84-item GSHS questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…In our study, we observed a prevalence of 18.6% for last-year suicidal ideation, 8.7% for suicidal plan, and 5.4% for suicidal attempt among the university student population. These findings are comparable with the studies conducted in high-income countries such as the United States, 27 Taiwan, 36 and Canada, 37 as well as studies in low-income countries of the Benin, 38 Lebanon, 39 and Tanzania. 28 Besides, this study findings support the existing evidence highlighting the association between FIS and suicidal behaviors among students.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we observed a prevalence of 18.6% for last-year suicidal ideation, 8.7% for suicidal plan, and 5.4% for suicidal attempt among the university student population. These findings are comparable with the studies conducted in high-income countries such as the United States, 27 Taiwan, 36 and Canada, 37 as well as studies in low-income countries of the Benin, 38 Lebanon, 39 and Tanzania. 28 Besides, this study findings support the existing evidence highlighting the association between FIS and suicidal behaviors among students.…”
Section: Discussionsupporting
confidence: 88%